THE USE OF YOUTUBE ENGLISH EDUCATIONAL VIDEOS IN IMPROVING LISTENING COMPREHENSION - Hanna Theresia Rehulina Sembiring; Caroline Victorine Katemba (UIBU, 2023)
This research aims to find out how students can use YouTube's educational English videos to enhance their listening skills. A Google Form online survey was used as the survey methodology for this quantitative research. The target population for this research is senior high school students taking English classes. Due to the application's beneficial effects on the student's hearing, the data analysis showed that the student can enhance their listening comprehension with YouTube's educational English videos. The results of this research suggest that watching English instruction videos on YouTube can improve students' listening comprehension. The results were supported by every student, who agreed that using YouTube to improve their listening comprehension could be helpful. This research is far from perfect and still has many flaws. The researcher therefore expects that another researcher will continue their study into how to use YouTube's application for English educational videos more effectively, especially in listening comprehension across a range of academic levels. The study's benefits and potential to help other researchers who want to look into a connected topic are also anticipated by the researcher.